LAWS IN BEHAVIOUR OF NonLTE EFFECTS FOR THE NaI AND Mgl ATOMS FOR K - A STARS - Mashonkina, L. I.; Shimanskaya, N. N.; Shimansky, V. V. (Одеські астрономічні публікації, 2017)
NonLTE calculations for the Nal and Mgl atoms were performed for model atmospheres of Tef= 4000 - 12000K. logg = 0.0 - 4.5, [NI/H] = 0.5- (-4). Departures from LTE result in strengthening the Nal spectral lines and weakening the Mgl ones. For 8 Nal spectral lines and 9 Mgl ones used usually in abundances determinations nonLTE abundance corrections were found. They are very individual for each spectral line and for specific parameters of stellar atmosphere. Even for the weakest spectral lines they are not small: they can reach to (-0.15dex) for the Nal λλ615.4, 616.0nm and 0.17dex for the Mgl λ457.1nm, λ571.1nm. The errors in abundances will be particularly large in the case of metal deficiency stars because the strong spectral lines are used in abundances determinations: for the Nal resonance lines nonLTE abundance corrections reach to (-0.8deX) and for the λλ517.2, 518.3nm they consist of 0.3dex. We conclude that nonLTE analysis is necessary in each case of sodium or magnesium abundance determination.